Pest management in store grains: (Acc: 5509) - Narayanasamy, P., Mohan, S., Awaknavar, J S.; Narayanasamy, P., 1937-; Mohan, S., Prof.; Awaknavar, J. S. (New Delhi : Satish Serial Pub. House, 2009)
Contributed seminar articles held at the Dept. of Entomology, Annamalai University during March 26-27, 2007
Keywords: Grain; Grain